Effect of Multiple‐Dose Diltiazem on the Pharmacokinetics of the Renin Inhibitor ACT‐077825. Issue 2 (16th March 2013) - Dingemanse, Jasper; Nicolas, Laurent B.; van Bortel, Luc
Abstract This open‐label, randomized study evaluated the effects of steady‐state diltiazem on the pharmacokinetic, safety, and tolerability profile of a single dose of the novel renin inhibitor ACT‐077825. Twelve healthy Caucasian male subjects (20–50 years) received in treatment sequence A, a single dose of 100 mg ACT‐077825 (Days 1 and 17), and oral diltiazem 300 mg once daily (Days 14–26). In treatment sequence B, subjects received a single dose of 100 mg ACT‐077825 (Days 4 and 22) and oral diltiazem 300 mg once daily (Days 1–13). ACT‐077825 alone and combined with diltiazem was generally well tolerated. On average, the systemic exposure to ACT‐077825 was higher in the presence of diltiazem. For AUC0–∞ and t1/2, the upper limit of the 90% confidence interval (CI) of the geometric mean ratios was outside the study‐specific 0.5–2.0 equivalence boundaries, that is, 1.92 (90% CI: 1.30, 2.83) and 1.58 (90% CI: 1.22, 2.04), respectively. In conclusion, diltiazem markedly affected the pharmacokinetics of ACT‐077825, probably via inhibition of CYP3A4 activity, without changing its safety and tolerability profile in healthy male subjects. Whether such an interaction will require for therapeutic dose adjustment of ACT‐077825 co‐administered with diltiazem has to be assessed once the dose‐response relationship of ACT‐077825 in hypertensive patients is determined.